Analisis Pengaruh Kualitas dan Profesionalisme terhadap Kinerja Karyawan pada Toko Bahan Bangunan - Hayati, Annisa Dewi; Said, Meldasari; Arifin, Zainal; Firdausi, Iqbal (Universitas Ibn Khaldun Bogor, 2024)
During the covid-19 recovery period, demand for building materials continued to increase along with improvements in the property and construction sectors. Therefore, companies or industries need to develop human resources of good quality and high professionalism in order to produce optimal performance. However, in reality there are still many workers in each company who do their work less effectively, especially in small companies such as building shops which do not have an organizational structure and are only owned by one individual. The purpose of this study is to ascertain and evaluate the impact of human resource quality and work professionalism on the performance of building shop employees. The population of this study were employees of building business shops in Angsana, Tanah Bumbu. Saturated sampling is used in the sampling process. There were thirty responders, or samples, obtained. Multiple linear regression is the data analysis approach that is being employed. Simultaneous and partial research The variables of work professionalism and the quality of human resources have a good and significant impact on employee performance, according to the data of building material shops employees.